New Energy Policies and Informal Cultural Norms Promoting Carbon Equity in Chinese Cities: Synergistic Effects and Regional Heterogeneity - Zixuan Yang; Huang Yu; Jingqiu Zhang (Energies)
In the era of energy transition, there is a lack of targeted research on the synergistic effects of new energy policies and informal institutions on carbon equity. This study examines how new energy policies influence urban carbon equity, with a focus on the mediating role of cultural forces. Utilizing panel data from 256 Chinese cities (2000–2021) and employing the New Energy Demonstration City (NEDC) policy as a quasi-natural experiment, this study adopts a staggered difference-in-differences (DID) approach to identify causal relationships. Key findings reveal: (1) China has been accompanied by a rise in carbon distribution inequity measured through the cumulative distribution patterns of carbon emissions and economic outcomes, highlighting the equity-efficiency trade-off. (2) The NEDC policy, while advancing energy transition, inadvertently exacerbates urban carbon inequity. The conclusion is robust to parallel trend tests, placebo analyses, and controls for concurrent policies. (3) Confucianism, as an informal institutional force, can effectively mitigate the urban policy-driven inequities. (4) Heterogeneity analysis finds that the synergistic effect of Confucianism and the policy is more significant in non-old industrial base cities and non-resource-dependent cities. Theoretically, this research bridges energy transition literature with institutional theory by revealing the compensatory role of cultural systems in formal policy frameworks. Practically, it advocates for culturally informed energy governance models, proposing Confucian principles of harmony and collective responsibility as design pillars for equitable sustainability transitions.